Photoelectron circular dichroism (PECD) of monoterpenes using laser and synchrotron radiation - Ganjitabar, Hassan (2020)
The asymmetry in the photoelectron angular distribution (PAD) with respect to the propagation direction of light, known as Photoelectron Circular Dichroism (PECD), is a very important property of the chiral molecules, which can be exploited for analytical purposes. PECD can be used as a probe to several static (chemical substitution, conformation, dimerization, and clustering) and dynamic (vibrational motions, intermediate and cationic electronic states as well as photoelectron kinetic energy) phenomena as it is sensitive to all of them. In this project, the focus was on the dynamic ones; the dependency of PECD on vibrational motions and decouple that from the other dynamic effects like photoelectron kinetic energy is investigated. The other major part of the project was to introduce a new method to simultaneously measure the chemical composition (cc) and enantiomer excess (ee) in gas phase mixtures. The idea with the cc analysis was that the photoelectron spectrum of a mixture must be a linear combination of the photoelectron spectra of its compounds. Similarly, the PECD spectrum of the mixture can be presented as a linear combination of the weighted PECD spectra of the compounds. The cc and ee of two essential oils, black pepper oil and Mexican lime oil, are studied as the benchmark. These two oils are mainly composed of volatile samples, a monoterpene family including α-pinene, β-pinene, limonene, 3-carene, sabinene and γ-terpinene, all of which are chiral except the last one. For cc analysis, we measured the high-resolution photoelectron spectra of the oils and their compounds at the DESIRS beamline of the SOLEIL synchrotron using Slow Photoelectron Spectroscopy (SPES) technique. We also measured the Velocity Map Imaging (VMI)-PES and VMI-PECD of the oils and their compounds at two fixed photon energies, h